Mobile-assisted English language learning for young learners during COVID-19 distance learning: Teachers’ experiences and voices - Misdi; Anisa Andiani Ramadina; Nor Syamimi Iliani Che Hassan; Kardi Nurhadi (Register Journal, 2023)
Despite a number of previous studies investigating online learning during the COVID-19 outbreak, more needs to be reported about TEYL teachers’ insightful experiences in photovoice. To fill this gap, the current phenomenological case study aimed at exploring TEYL teachers’ experiences in enacting MALL during the distance learning period amidst the COVID-19 pandemic using photovoice. Two teachers were recruited as the study participants. The data were garnered from the participants’ photovoice collections depicting critical incidents and interviews. The results showed that MALL was perceived as a powerful instructional method in distance English learning amidst the COVID-19 pandemic. The teachers reported that they encountered several obstacles caused by unstable internet networks, difficulty in direct supervision of young learners, and the requirement of extra effort to prepare interesting teaching materials. On a positive note, MALL has benefited the teachers by enriching their experiences using various mobile applications for their English language instructions. The enactment of MALL has also foregrounded parents’ important roles in monitoring their children’s use of mobile devices. Drawing from the findings, this research implies that photovoice can be used to explore teachers' and students’ life experiences with distance learning in Indonesian teacher education.